Biomechanical evaluation of back injuries during typical snowboarding backward falls - Wei, W.; Evin, M.; Bailly, N.; Arnoux, P. (Scandinavian Journal of Medicine & Science in Sports, 2022)
To prevent spinal and back injuries in snowboarding, back protector devices (BPDs) have been increasingly used. The biomechanical knowledge for the BPD design and evaluation remains to be explored in snowboarding accident conditions. This study aims to evaluate back-to-snow impact conditions and the associated back injury mechanisms in typical snowboarding backward falls. A previously validated snowboarder multi-body model was first used to evaluate the impact zones on the back and the corresponding impact velocities in a total of 324 snowboarding backward falls. The biomechanical responses during back-to-snow impacts were then evaluated by applying the back-to-snow impact velocity to a full human body finite element model to fall on the snow ground of three levels of stiffness (soft, hard, and icy snow). The mean values of back-to-snow normal and tangential impact velocities were 2.4 m/s and 7.3 m/s with maximum values up to 4.8 m/s and 18.5 m/s. The lower spine had the highest normal impact velocity during snowboarding backward falls. The thoracic spine was found more likely to exceed the limits of flexion-extension range of motions than the lumbar spine during back-to-snow impacts, indicating a higher injury risk. On the hard and icy snow, rib cage and vertebral fractures were predicted at the costal cartilage and the posterior elements of the vertebrae. Despite the possible back injuries, the back-to-snow impact force was always lower than the force thresholds of the current BPD testing standard. The current work provides additional biomechanical knowledge for the future design of back protections for snowboarders.